PERFORMANCE OF SUSTAINABLE CONCRETE CONSTRUCTED WITH LOCALLY AVAILABLE AGGREGATES - ALNAFFAKH, MOHAMMAD REDHA I.; ALGHAZALI , HAYDER H. (Journal of Duhok University, 2023)
As is desired, more sustainable concrete has become the target of many infrastructural engineers. To produce more sustainable concrete, it should take into account the materials’ cost and CO2 footprint. Coarse aggregate occupies more than 60% of concrete’s weight, making it the most consumed component. The majority of quarries that produce coarse aggregate are far away from cities, so the necessary transportation operations increase carbon dioxide emissions and the cost of the materials. Therefore, it has become necessary to find alternatives for these coarse aggregate types presently in use. In this study, five coarse aggregate types: three new types (limestone aggregate, white crushed stone, and white rounded gravel) were selected as coarse aggregate in concrete mixtures besides the two common coarse aggregate types (black round and crushed black aggregates) to investigate the bond behavior of the aggregates with steel rebar. A ranking analysis approach was adopted to examine the performance of the new aggregate types. Test results reveal that the new aggregate types perform well in bond strength and can be adopted in civil structural applications.